The genus Leucophenga (Diptera, Drosophilidae), part IV: the ornata species group from the East Asia, with morphological and molecular evidence (II) - Huang, Jia; Li, Tong; Chen, Hongwei (Zootaxa, 2014)
Twenty-one species of the Leucophenga ornata species group are surveyed (including 12 new species): L. atrinervis Okada, 1968; L. digmasoma Lin & Wheeler, 1972; L. multipunctata Chen & Aotsuka, 2003; L. nigrinervis Duda, 1924; L. pectinata Okada, 1968; L. pentapunctata Panigrahy & Gupta, 1982; L. quadripunctata (de Meijere, 1908); L. regina Malloch, 1935; L. trivittata Okada, 1990; L. acutifoliacea sp. nov.; L. albiterga sp. nov.; L. angustifoliacea sp. nov.; L. baculifoliacea sp. nov.; L. cornuta sp. nov.; L. hirticeps sp. nov.; L. latifascia sp. nov.; L. pinguifoliacea sp. nov.; L. retihirta sp. nov. L. securis sp. nov.; L. sinupenis sp. nov.; L. villosa sp. nov.; these species (except for L. baculifoliacea sp. nov.) having pubescence on the distal portion of aedeagus. A key to all the examined species of the ornata group in this study is provided. We try to improve our species delimitation by integrating the DNA sequences data with morphological information. The intra- and interspecific pairwise K-2P (Kimura’s two-parameter) distances are summarized.